Optic nerve sheath diameter in severe preeclampsia with neurologic features versus controls - Mary E. Sterrett; Brittany Austin; Ryan M. Barnes; Eugene Y. Chang (BMC, 2022)
Abstract Background Optic nerve sheath diameters (ONSD) have been validated as an accurate screening tool to detect elevated intracranial pressure in hypertensive encephalopathy. The neurologic manifestations of preeclampsia and/or eclampsia mimic those of hypertensive encephalopathy. This study was performed to assess the incidence of elevated optic nerve sheath diameters of patients with severe preeclampsia and neurologic criteria compared to non-preeclamptic patients. The secondary objective was to determine baseline optic nerve sheath diameters in patients with severe preeclampsia without neurologic criteria and preeclampsia without severe features. Methods Single site cohort study including 62 pregnant women 18 years or older and 20 weeks or further gestation. Patients with preeclampsia without severe features, preeclampsia with severe features by non-neurologic criteria, preeclampsia with severe features with neurologic criteria, and patients without preeclampsia were enrolled via convenience sampling. One blinded reviewer measured sheath diameters; baseline demographics and pregnancy data were collected by chart review. Statistical analysis was completed with STATA/IC 16. Categorical variables were compared by the χ2 test. Continuous variables were presented as mean ± standard deviation, and discrete variables were presented as medians and compared by Kruskal-Wallis testing. Normality was confirmed by Shapiro-Wilk testing. Linear and logistic regression were used to test the association between the preeclampsia groups and optic nerve sheath diameters. Models were presented as unadjusted and adjusted for BMI, gestation, hypertension, diabetes, parity, and gravidity. Results The incidence of optic nerve sheath diameters > 5.8 mm was 43.8% in the severe preeclampsia with neurologic features cohort, and 42.1% in the control cohort, with a relative risk of 1.04. Patients with severe preeclampsia without neurologic features had sheath diameters of 5.75 mm ± 1.09 mm; non-severe preeclampsia patients had sheath diameters of 5.54 mm ± 1.26 mm. Conclusions We did not find a significant elevated optic nerve sheath diameter relative risk between severe preeclampsia patients with neurologic features and non-preeclampsia control patients. This is the first study to assess a North American population utilizing ACOG criteria for severe and non-severe preeclampsia, with severe cohorts additionally stratified by neurologic criteria.